2010
DOI: 10.1103/physrevlett.105.212503
|View full text |Cite
|
Sign up to set email alerts
|

Isospin Character of the Pygmy Dipole Resonance inSn124

Abstract: The pygmy dipole resonance has been studied in the proton-magic nucleus 124 Sn with the (α, α ′ γ) coincidence method at Eα = 136 MeV. The comparison with results of photon-scattering experiments reveals a splitting into two components with different structure: one group of states which is excited in (α, α ′ γ) as well as in (γ, γ ′ ) reactions and a group of states at higher energies which is only excited in (γ, γ ′ ) reactions. Calculations with the self-consistent relativistic quasiparticle timeblocking ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
135
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 35 publications
17
135
0
1
Order By: Relevance
“…This observation is a clear indication for a change of structure in the low-lying E1 strength. The same pattern has been observed in 94 Mo [26], 124 Sn [27,28], and 138 Ba [29]. Figure 2 provides an overview of the data, showing the comparison of the results of the corresponding (α, α γ) and (γ, γ ) experiments for each nucleus.…”
Section: Results From Hadron Scatteringmentioning
confidence: 59%
See 1 more Smart Citation
“…This observation is a clear indication for a change of structure in the low-lying E1 strength. The same pattern has been observed in 94 Mo [26], 124 Sn [27,28], and 138 Ba [29]. Figure 2 provides an overview of the data, showing the comparison of the results of the corresponding (α, α γ) and (γ, γ ) experiments for each nucleus.…”
Section: Results From Hadron Scatteringmentioning
confidence: 59%
“…The comparison to microscopic QPM and RQTBA calculations shows a qualitative agreement using the proper isoscalar (IS) E1 operator to compare to the (α, α γ) data and the EM operator for the NRF results [27]. Based on this agreement conclusions on the nature of the E1 strength can be drawn using the calculated transition densities of the corresponding excitations.…”
Section: Results From Hadron Scatteringmentioning
confidence: 73%
“…Combined (γ, γ ) and (α, α γ) experiments on the open shell 124 Sn [11,12,28] found that the low-lying dipole strength splits into an upper sector composed of isovector transitions promoted by γ's and a lower region of levels populated by both α's and γ's. Only these low-lying peaks form therefore the PDR.…”
Section: Calculations and Resultsmentioning
confidence: 99%
“…In stable nuclei, dense discrete spectra of dipole states were detected in (γ, γ ) [3][4][5][6][7][8][9] and in (α, α γ) experiments [10][11][12]. Moreover, fairly complete dipole spectra below and above the neutron decay threshold were produced with great accuracy through inelastic proton scattering experiments [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…Aiming at isospin characters of these 1 − states, it has been demonstrated that the complementary studies of real-photon scattering and high-resolution (α, α γ) coincidence experiments at 136 MeV allow separating isovector and isoscalar dipole response which is important for a deeper understanding of the underlying mechanisms generating the dipole strength [2]. Systematic studies using these complementary probes revealed a splitting into low-lying isospin-mixed E1 excitations and higher-lying dominantly isovector E1 excitations in neutron-magic, proton-magic, and non-magic nuclei (namely 140 Ce, 138 Ba, 124 Sn, and 94 Mo) [2][3][4][5]. This experimentally observed common feature of the low-lying E1 response is reproduced by several theoretical calculations (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%